PENGARUH PENGENDALIAN INTERN TERHADAP EFEKTIVITAS TARGET PRODUKSI PT. LUCAS DJAJA PHARMACEUTICAL INDUSTRY BANDUNG JAWA BARAT - Fitria, Bulan Tati; Prissilia, Kania (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The achievement of operational targets is expected by each organization / company. Due to the achievement of the target, it can be judged that the performance of the company very well. Therefore, if it is not achieved it is necessary to study the factors that influence it. For then do repairs on these factors. In the achievement of the target company, it takes a process associated with the target to be achieved. In order to achieve maximum results and effective it is necessary to an adequate internal control structure, which aims to regulate the operational steps the company to run an organized and effective.The study was conducted at PT. Lucas Djaja Pharmaceutical Industry, located in Bandung, is to know how the implementation of internal controls and how they affect the effectiveness of the production targets, in particular the production of injection of 1 (one) milliliter. This research used descriptive analysis with research techniques such as interviews, observations, questionnaires and literature study. Based on the results of this study concluded that the implementation of internal control at PT. Lucas Djaja is sufficient, this can be seen from the data obtained from the questionnaire filled out by the respondents, which is related to the control environment, risk assessment, information and communication, control activities, and monitoring. Meanwhile that of the effectiveness of the production target is still this can be seen from the data obtained from the questionnaire filled out by the respondents, ranging from productivity, quality, efficiency, flexibility, excellence, development, and satisfaction. And the obtained results of the research stating that the internal control effect on effectiveness production targets with determination coefficient of 56.01% and the remaining 43.99% influenced by other factors.